2008
DOI: 10.1590/s0004-27302008000200004
|View full text |Cite
|
Sign up to set email alerts
|

Marcadores genéticos e auto-imunes do diabetes melito tipo 1: da teoria para a prática

Abstract: Type 1 A diabetes mellitus (T1AD) results from the autoimmune destruction of the insulin producing pancreatic beta-cells. The largest contribution to genetic susceptibility comes from several genes located in the major histocompatibility complex on chromosome 6p21.3 (IDDM1 locus), accounting for at least 40% of the family aggregation of this disease. The highest-risk human leukocyte antigen HLA genotype for T1AD is DR3-DQA1*0501-DQB1*0201/DR4-DQA1*0301-DQB1*0302, whereas -DR15-DQA1*0102-DQB1*0602 haplotype is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
2
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
6
2
10
Order By: Relevance
“…10 However, in the present study, we observed that 63.8% of a study population that had been diagnosed with DM1 more than three years previously and was on insulin therapy was anti-GAD-positive.…”
contrasting
confidence: 64%
“…10 However, in the present study, we observed that 63.8% of a study population that had been diagnosed with DM1 more than three years previously and was on insulin therapy was anti-GAD-positive.…”
contrasting
confidence: 64%
“…Previous studies conducted in Brazil with small sample sizes have shown inter-regional differences in the frequencies of the HLA-DR and -DQ alleles and of the other risk polymorphisms for T1D3. Furthermore, differences in populations referred to as Caucasian in other countries were also observed14.…”
Section: Discussionmentioning
confidence: 89%
“…Skin color is poorly correlated with genetic ancestry in the Brazilian population and therefore self-reported race can be inaccurate for genetic studies [Pena, et al 2011]. Early genetic studies of type 1 diabetes (T1D) in Brazilians reported geographic variability in HLA-DR and HLA-DQ allele frequencies, two genetic loci strongly associated with T1D in Europeans [Silva, et al 2008; Thomson, et al 2007]. In a study accounting for PS, Gomes et al identified a novel protective haplotype DRB1*10-DQB1*0501 [Gomes, et al 2017].…”
Section: Key Conceptsmentioning
confidence: 99%